2020
DOI: 10.1063/5.0008015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pd/MoOx/n-Si diodes for bipolar transistor and light-emitting device applications

Abstract: Sub-stoichiometric molybdenum oxide (MoO x ) has recently been investigated for application in high efficiency Si solar cells as a "hole selective" contact. In this paper, we investigate the electrical and light-emitting properties of MoO x -based contacts on Si from the viewpoint of realizing functional bipolar devices such as light-emitting diodes (LEDs) and transistors without any impurity doping of the Si surface. We realized diodes on n-type Si substrates using e-beam physical vapor deposition of Pd/MoO x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…For negative bias we observe a linear dependence of 1/C 2 with the applied voltage for frequencies from 20 kHz to 500 kHz. This behavior was previously observed by Gupta et a [25]. for Pd/MoO x /n-Si junctions in the 10 khz-…”
supporting
confidence: 85%
See 1 more Smart Citation
“…For negative bias we observe a linear dependence of 1/C 2 with the applied voltage for frequencies from 20 kHz to 500 kHz. This behavior was previously observed by Gupta et a [25]. for Pd/MoO x /n-Si junctions in the 10 khz-…”
supporting
confidence: 85%
“…The proposed band diagram of this type of solar cells is very similar to a Schottky junction [20]. Some authors, like Gupta et al studied this approach in Pd/MoOx/n.Si diodes [25]. In a previous work, we measured the currentvoltage characteristics at different temperatures for a MoO x based solar cell obtaining similar results.…”
Section: Resultssupporting
confidence: 58%
“…This means that at a certain forward bias voltage, the hole current will saturate and no longer increase exponentially with the voltage. This effect may be difficult to identify in the measurements because the high current also means that the series resistance has a large impact and can attenuate the current already at low forward voltages [110,111]. In Fig.…”
Section: Lateral Pnp Transistorsmentioning
confidence: 99%
“…However, in reality, chemical reactions at the metal-silicon interface will often modify the experimentally observed SBH [23]. Much work has been devoted to developing layers between the metal and Si to disrupt this effect and nevertheless get either a low SBH, mainly for the purpose of making more low ohmic contacts [24], or, oppositely, a high SBH for increasing hole injection and/or reducing electron injection [25]. In this paper, it was also demonstrated that in simulations of experimental results, the effect of the interface and surrounding (charged) layers can often be reproduced by assuming the diode to have an appropriate SBH and surface recombination velocity.…”
Section: Theoretical Considerationsmentioning
confidence: 99%